The Association Between Coronary Artery Disease and Type 2 Diabetes Mellitus in Libyan Adults: A Cross-Sectional Study - Razk Abdalgwad; Ali Fadhlullah; Ahmed Balha (Khalij-Libya Journal of Dental and Medical Research, 2022)
Background and objectives. Diabetes mellitus is a highly prevalent chronic multisystem disease and it has a significant impact on the health of many important organs in our body, including the cardiovascular system (CVS). This study aimed to determine the association between Type 2 diabetes mellites (T2DM) and the development of coronary artery disease (CAD). Methods. A retrospective cross-sectional study was conducted on patients who were diagnosed with CAD and T2DM. We examined the likelihood occurrence of CAD in T2DM patients using the Bayesian one sample test. Results. About 97 patients were confirmed to have CAD and were included in the study. The mean age of participants was 60±11.89. Approximately, 53 (54.6%) of patients were females, while 44 (45.4%) were males. The vast majority of patients had T2DM and CAD at 69 (71.1%) as opposed to only 28 (28.9%) of patients who did not have T2DM but had CAD. Moreover, there was a statistically significant increase in the likelihood of occurrence of CAD amongst the T2DM group. The percentage of patients who have T2DM with CAD was significantly higher than those who were not diagnosed with T2DM but had CAD at 69 (71.1%) compared to 28 (28.9%) (P = 0.002) for the group of T2DM concomitant with CAD, and the group of non-T2DM concomitant with CAD, respectively. Conclusion. There was a significant relationship between T2DM and CAD, suggesting the importance of intensive glycemic control in diabetic patients possibly via lifestyle modifications or medications in order to reduce or delay the possibility of occurrence of CAD amongst diabetic patients, in particular.